The US position on the Indo-Pakistan war of 1971 - Al-Dulaimi, Muhammad Faihan Musa (The International and Political Journal, 2022)
The American position in the Indo-Pakistani war in 1971 is one of the important positions that have a great influence in the Middle East, especially the South Asia region. South Asia had gained special importance in American foreign policy because of the influence of race that existed at the time with the Soviet Union despite that The United States of America attempted to be neutral and not stand by one side at the expense of the other. America was linked to Pakistan with several agreements (security, trade or defense) and it was clear that the influence of the United States of America is increasing where its interests and where do they lie, and it would have been better for it to stand by Pakistan because there were some alliances between them.